Hidden double excitations in the oxygen inner-shell ionization continuum of CO - R Püttner; D Céolin; O Travnikova; J Palaudoux; M Hoshino; H Kato; H Tanaka; Y Tamenori; C C Wang; C Miron; K Ueda; M N Piancastelli (New Journal of Physics, 2013)
Auger decay spectra of CO subsequent to O 1s ionization with 549.85 eV photons, i.e. close to the top of the shape resonance, are presented. Their comparison with the normal Auger spectrum recorded at a photon energy well above the shape resonance reveals distinct features. In particular, in the energy region of the O 1s ^−1  →  b ^1 Π and O 1s ^−1  →  a ^1 Σ ^+ Auger transitions which are well known to consist of vibrational progressions, additional narrow lines are revealed by the spectra recorded at 549.85 eV. In a detailed fit analysis of these Auger spectra it was possible to show that the newly found lines do not exhibit the expected distortions caused by post-collision interaction. This observation identifies these lines as caused by a different mechanism, such as resonant Auger decay processes of doubly excited states. The transitions are assigned using energy and intensity arguments in combination with complementary angular distribution measurements for the Auger electrons.